Preparation method of moisture-proof crosslinked polyethylene insulating material

By using the cross-linking reaction of urethane polyethylene and silane coupling agent in the insulating material, a moisture-proof cross-linked polyethylene insulating material with hydrophobicity and high toughness is formed, which solves the problem of insulating material being damp in a humid environment. Improves the moisture resistance and shelf life of the material.

CN119161515APending Publication Date: 2024-12-20ANHUI ZHONGQING XINYI ALUMINUM ALLOY CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411253228.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing insulating materials are prone to moisture in humid environments, resulting in aging of cable insulation, increasing safety hazards and degradation of transmission performance, and it is difficult to completely remove moisture, affecting product quality.

Method used

Using the combination of urethane polyethylene, silane coupling agent and crosslinking agent, the crosslinking reaction is carried out through the action of catalyst and initiator to form a moisture-proof crosslinking polyethylene insulating material with hydrophobicity and high toughness, reducing air The contact area of ​​moisture enhances the moisture resistance of the material.

Benefits of technology

It improves the hydrophobicity and aging resistance of the insulating material, extends the shelf life, reduces the risk of moisture, enhances the adhesion to metal and surface finish, and is suitable for cable insulation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of insulating materials, in particular to a preparation method of a moisture-proof crosslinked polyethylene insulating material, which specifically comprises the following steps: (1) preparing a catalyst master batch; (2) preparing a silane auxiliary agent; (3) preparing a finished product; (3.1) proportionally sucking the carbamate polyethylene and the catalytic master batch into a stirrer in parts by mass for mixing, and sucking into a drying tower for drying after uniformly mixing, so as to obtain a raw material A; (3.2) adding the raw material A and the silane additive into a twin-screw extruder, adding an initiator, and grafting the materials on a twin-screw extruder; (3.3) extruding, granulating, dehydrating and drying the material subjected to double-screw grafting by a single screw, and feeding the material into a finished product bin; and (3.4) metering and packaging to obtain a finished product. Experiments prove that the material prepared by the invention not only has the characteristics of the original silane crosslinked polyethylene, but also has the advantages of easiness in storage, moisture resistance and high surface smoothness of extruded plastic, and is suitable for replacing the original crosslinked polyethylene insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating materials, in particular to a method for preparing a moisture-proof cross-linked polyethylene insulating material. Background Art

[0002] In cable manufacturing, in addition to the cost of conductor materials, the cost of insulation materials also accounts for a high proportion. However, plastic, as a rough and porous material, easily absorbs moisture in the air and becomes damp. The existing technology is to dry it during the production process to remove internal moisture and impurities, and to tightly package it during transportation and storage to reduce the possibility of moisture, and then place it in a ventilated and dry place with a desiccant.

[0003] However, the shelf life of plastic granules for cables using this method generally does not exceed 6 months. In reality, in the humid environment of the south (the return of the south wind or the plum rain season), it is difficult to ensure humidity control, and it is common for the plastic granules to become damp within one or two months. Once the plastic granules become damp, they need to be dried before production, which is time-consuming and labor-intensive, and it is difficult to completely remove moisture, thus affecting the quality of the cable products.

[0004] Harm of cable damp: ① Potential safety hazards: Water molecules gather at microscopic defects in the insulation layer under the action of the electric field to form pores, and eventually form water trees inside the insulation of the cable. The appearance of water trees causes a significant decrease in the insulation level and breakdown voltage of the cable; when the system is overvoltage, the water trees can easily transform into electrical trees, which will break down the insulation, causing leakage and power outages, and even fires.

[0005] ② Accelerated insulation aging: Even if water trees or electrical trees are not formed, aging of the cable insulation layer is inevitable. If the cable is invaded by moisture, the moisture will accelerate the aging of the insulation layer, thus affecting the service life of the cable.

[0006] ③ Impact on transmission performance: The cable is affected by moisture, which affects the cable transmission performance, such as poor signal shielding ability and shortened transmission distance.

[0007] To prevent cables from getting damp, one is to maintain a dry and ventilated environment during laying and installation to prevent cable damage, especially the sealing and waterproofing of cable joints; the second is to make the cable materials moisture-proof to eliminate the influence of water molecules in the cable insulation layer from the source. Summary of the invention

[0008] In order to solve the problems raised in the above background technology, the present invention provides a method for preparing a moisture-proof cross-linked polyethylene insulating material.

[0009] A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 140-180° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) 100 parts of urethane polyethylene and 0.2-0.4 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 30-60 minutes to obtain raw material A; (3.2) Add the raw material A and 0.3-5 parts of the silane auxiliary agent into a twin-screw extruder, and add 0.03-0.2 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0010] Specifically, carbamate is used as an amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, the pressure is increased to 15 to 30 atmospheres, the reflux temperature is heated to 97 to 106°C, the heating time is 18 to 24 hours, then ice-bathed, and concentrated hydrochloric acid is added to precipitate to obtain the product.

[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention introduces carbamate functional groups through polyethylene ammonium reaction, which has hydrophobicity, provides surface smoothness of insulating plastic particles, and increases adhesion to metal (aluminum); 2. Under the action of copper catalyst, carbamate can make linear and branched polyethylene aminated without chain breaking. After ammoniation, chemical cross-linking is carried out, resulting in polyethylene with a new combination of functional groups and structures. The synthesized material has adjustable volume and surface properties, which improves the toughness of the insulation material wrapping, adhesion to metal and surface smoothness, and reduces the contact area with water molecules in the air. The addition of hydrophobic groups also changes the performance of polyethylene and enhances the hydrophobicity of polyethylene.

[0012] 3. The normal principle of polyethylene chemical cross-linking is a series of free radical reactions triggered by the high temperature decomposition of peroxide, which then causes PE to cross-link. Peroxide decomposes under heat to form free radicals, and the cross-linking reaction process is as follows:

[0013] The preparation process of silane cross-linked polyethylene in the present invention includes grafting silane containing unsaturated vinyl groups and easily hydrolyzed alkoxy multifunctional groups onto the main chain of polyethylene, then, the grafted product is hydrolyzed under the action of water and a silanol condensation catalyst, and condenses to form ~Si—O—Si~ cross-linking bonds, thereby obtaining silane cross-linked polyethylene, and then performing a silane cross-linking reaction to increase the intermolecular force, effectively improve the strength, tensile strength and aging resistance of the insulating material, and obtain a new polyethylene insulating material for wires and cables. The material not only has the characteristics of the original silane cross-linked polyethylene, but also has the advantages of easy storage, moisture resistance, and high surface finish of the extruded plastic, and is suitable for replacing the original cross-linked polyethylene insulating material. DETAILED DESCRIPTION

[0014] Example 1

[0015] A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 140° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) 100 parts of urethane polyethylene and 0.2 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 30 minutes to obtain raw material A; (3.2) Add the raw material A and 0.3 parts of the silane auxiliary agent into a twin-screw extruder, and add 0.03 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0016] Specifically, carbamate is used as the amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, pressurized to 15 atmospheres, heated to reflux temperature of 97°C, heated for 18 hours, then ice-bathed, and concentrated hydrochloric acid is added to precipitate to obtain the product.

[0017] Example 2 A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 180° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged and temporarily stored in a vacuum aluminum-plastic bag to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) By weight, 100 parts of urethane polyethylene and 0.4 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 60 minutes to obtain raw material A; (3.2) Add the raw material A and 5 parts of the silane additive into a twin-screw extruder, and add 0.2 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0018] Specifically, carbamate is used as the amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, the pressure is increased to 30 atmospheres, the reflux temperature is heated to 106°C, the heating time is 24 hours, then the mixture is placed in an ice bath, and concentrated hydrochloric acid is added to precipitate the mixture.

[0019] Example 3 A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 160° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) 100 parts of urethane polyethylene and 0.3 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 40 minutes to obtain raw material A; (3.2) Add the raw material A and 2 parts of the silane additive into a twin-screw extruder, and add 0.1 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0020] Specifically, carbamate is used as the amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, the pressure is increased to 20 atmospheres, the reflux temperature is heated to 100°C, the heating time is 20 hours, then an ice bath is placed, and concentrated hydrochloric acid is added to precipitate the product.

[0021] Example 4 A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 170° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) By weight, 100 parts of urethane polyethylene and 0.3 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 50 minutes to obtain raw material A; (3.2) Add the raw material A and 2.4 parts of the silane auxiliary agent into a twin-screw extruder, and add 0.11 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0022] Specifically, carbamate is used as the amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, pressurized to 25 atmospheres, heated to reflux temperature of 105°C, heated for 20 hours, then placed in an ice bath, and prepared by adding concentrated hydrochloric acid for precipitation.

[0023] Example 5 A method for preparing a moisture-proof cross-linked polyethylene insulating material is as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 1550° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) By weight, 100 parts of urethane polyethylene and 0.25 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 45 minutes to obtain raw material A; (3.2) Adding the raw material A and 4.2 parts of the silane additive into a twin-screw extruder, and adding 0.15 parts of an initiator, the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula:

[0024] Specifically, carbamate is used as the amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, the pressure is increased to 20 atmospheres, the reflux temperature is heated to 100°C, the heating time is 22 hours, then an ice bath is placed, and concentrated hydrochloric acid is added to precipitate the product.

[0025] Control group There is currently available silane cross-linked polyethylene insulation material.

[0026] The six insulating materials in the five embodiments and the control group were used to prepare the samples. The basic physical parameters of the six materials were roughly the same: density was 0.92 g / cm 3, the melt flow rate is 2.0g / (10min), the sample is cut into a square size of 10cm×10cm×1.0mm, and before testing, the sample is placed in a vacuum oven at 70℃ for 24h to remove cross-linking byproducts and residual stress.

[0027] Referring to GB / T2951.11-2008, a 20mm measuring area is marked in the middle of the sample, a weight is loaded at a pressure of 0.2MPa, and the sample is placed in a 200℃ oven for 15 minutes, and the load elongation is calculated; then the weight is quickly removed, and the sample is kept in the oven for 5 minutes, and the sample is taken out and cooled to room temperature in the air, and the permanent elongation is calculated. The results are as follows:

[0028] Referring to GB / T4207-2022, six kinds of insulating material samples were tested for tracking resistance index. The results are as follows:

[0029] The results show that the insulation materials in the five embodiments are significantly better than the insulation materials in the control group in terms of moisture resistance.

[0030] In summary, the material prepared by the present invention not only has the characteristics of the original silane cross-linked polyethylene, but also has the advantages of easy storage, moisture resistance, and high surface finish of the extruded plastic, and is suitable for replacing the original cross-linked polyethylene insulation material.

[0031] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0032] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a moisture-proof cross-linked polyethylene insulating material, characterized in that: The details are as follows: (1) Preparation of catalyst masterbatch Dibutyltin laurate maleate, di-n-octyltin dilaurate and dodecylbenzene are placed in a mixer and stirred, first at a low speed for 1 minute and then at a high speed for 3 minutes, and then poured into a hopper of a twin-screw extruder, the temperature of the twin-screw extruder is 140-180° C., after extrusion, cooled in a cooling water tank, and then dried by a fan before pelletizing, the pellets are dried in a drying tower at 80° C. for 2 hours, and finally packaged in a vacuum aluminum-plastic bag for temporary storage to obtain the catalyst masterbatch; (2) Preparation of silane additives The silane auxiliary agent is prepared by mixing a silane coupling agent, a crosslinking agent DCP and an antioxidant 300; (3) Finished product preparation (3.1) 100 parts of urethane polyethylene and 0.2-0.4 parts of the catalyst masterbatch are sucked into a mixer in proportion and mixed. After mixing evenly, the mixture is sucked into a drying tower and dried at 60° C. for 30-60 minutes to obtain raw material A; (3.2) Add the raw material A and 0.3-5 parts of the silane auxiliary agent into a twin-screw extruder, and add 0.03-0.2 parts of an initiator, and the above materials are grafted on the twin-screw; (3.3) The material grafted by the twin screw is extruded by a single screw, pelletized by eccentric water mist, and transported to the dehydrator by a conveying water pump. After dehydration, it is transported to the fluidized bed by a conveying fan. The material is fully dried by controlling the height of the material level, and finally sucked into the finished product silo by a vacuum suction machine; (3.4) The finished product is measured and packaged; Wherein, the urethane polyethylene is prepared by the following chemical formula: ; Specifically, carbamate is used as an amino reagent, carbamate and C2H4 are mixed in a ratio of 1:25 per molecule, di-tert-butyl peroxide (DTBP) is used as an oxidant, free Cu ions are used as a catalyst, the pressure is increased to 15 to 30 atmospheres, the reflux temperature is heated to 97 to 106°C, the heating time is 18 to 24 hours, then ice-bathed, and concentrated hydrochloric acid is added to precipitate to obtain the product.